Welfare and well-being social value in public policy - Jordan, Bill 1941- (Policy Press, 2008)
In this original book, Bill Jordan presents a new analysis of well-being in terms of its social value, and outlines ways in which this could be incorporated into public policy decisions
Title from publisher's bibliographic system (viewed on 21 Jan 2022)
Keywords: Social policy; Public welfare; Well-being; Social values